Case Report: Sclerosing angiomatoid nodular transformation of the spleen: surgery or conservative treatment? - Yan, Shuai; Wang, Zihan; Lu, Jiajie; Yuan, Liuxia; Ju, Linling; Wang, Huixuan; Chen, Lin; Cai, Weihua; Xiao, Feng; Wu, Jinzhu (Frontiers in Immunology, 2025)
Sclerosing angiomatoid nodular transformation (SANT)is a rare vascular sclerosing mass-like lesion, often discovered incidentally during routine imaging evaluation or during visits for the patient’s primary disease. SANT has complex pathological manifestations, unknown natural course of development and rarity, which makes it difficult for clinicians and pathologists to define its true nature. We report a 55-year-old male patient who came to see a doctor due to a physical examination accidentally found a spleen mass. He had hypertension and hyperlipidemia, and had no obvious clinical symptoms. After that, he underwent surgical resection of the spleen, and the patient had no special discomfort after treatment. Our results show that surgical resection is an efficient treatment for SANT patients without obvious clinical symptoms, but the patient ‘s comprehensive conditions should also be considered.